VIVER: A sustainable transport vision for Germany - Wolfgang Schade; Anja Peters; Claus Doll; Stefan Klug; Jonathan Hugh Köhler; Michael Krail (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2011)
VIVER (Live) - Vision für nachhaltigen Verkehr in Deutschland (A sustainable transport vision for Germany) is an internal research project of Fraunhofer ISI, initiated by the Business Unit Transportation Systems. The objective of the project was to come up with a clear vision of sustainable transport in Germany for the year 2050. In doing so, a conscious decision was made to only draw on the interdisciplinary expertise available within the Fraunhofer ISI. The result clearly shows that sustainable transport in Germany will only be achievable via a compatible combination of technological change and behavioural changes. In a sustainable transport system, passenger and freight transportation will not continue to grow up to 2050, but will stabilise over the next decades - passenger transport earlier than freight - and passenger transport will even decrease significantly in the final decades. This trend break from constantly growing transport demand to stagnation and decline can mainly be traced back to behavioural and structural changes in production and globalisation processes (i.e. ultimately to behavioural changes in companies). These changes can be explained by changing values in society on the one hand (e.g. in the direction of a greater importance of climate protection and quality of life) and, on the other hand, by changing framework conditions (e.g. due to an increased shortage of fossil energy sources) and political strategies (e.g. transport taxes, user charges and town planning based on environmental aspects). Technology change ensures that the remaining transport will be sustainable. Important aspects here include the broad diffusion of efficient drive technologies and lightweight construction and the associated introduction of new vehicle concepts both in passenger and freight transportation. The optimisation and intelligent design of multimodal mobility concepts via information and communication technologies also play an important role. For example, in passenger transport, these technologies will enable access to the respective optimal mode of transport with standardised real-time booking and invoicing interfaces; in freight transport they will allow the efficient combination of different means of transport and a much improved rate of utilisation and better route management. The combination of passenger and goods transport in one vehicle may also become more important in the future. The vision presented describes the result of moving towards a sustainable transport system. It can help to communicate sustainable development targets to the relevant target groups in society and is attractive and appealing instead of sparking fear of changes. – – VIVER (Leben) - Vision für nachhaltigen Verkehr in Deutschland ist ein Eigenforschungsprojekt des Fraunhofer ISI, initiiert durch das Geschäftsfeld Verkehrssysteme. Ziel des Projektes war es eine anschauliche Vision für nachhaltigen Verkehr in Deutschland für das Jahr 2050 zu entwerfen. Dabei wurde bewusst ausschließlich die interdisziplinäre Expertise des Fraunhofer ISI genutzt. Im Ergebnis wird deutlich, dass nachhaltiger Verkehr in Deutschland sich nur durch die passfähige Kombination von technologischem Wandel und Verhaltensänderung erreichen lässt. In einem nachhaltigen Verkehrssystem werden der Personen- und Güterverkehr nicht bis 2050 weiter wachsen, sondern sich in den nächsten Dekaden stabilisieren - der Personenverkehr früher als der Güterverkehr - und der Personenverkehr wird in den letzten Dekaden sogar deutlich zurückgehen. Dieser Trendbruch von stetig wachsender Verkehrsnachfrage hin zu Stagnation und Rückgang lässt sich vor allem auf Verhaltensänderungen und strukturelle Veränderungen in Produktions- und Globalisierungsprozessen (d.h. letztendlich auf Verhaltensänderungen der Unternehmen) zurückführen. Diese Veränderungen lassen sich zum einen durch einen Wertewandel in der Gesellschaft (z.B. hin zu einer hohen Bedeutung von Klimaschutz und Lebensqualität) und zum anderen durch veränderte Rahmenbedingungen (z.B. durch eine verstärkte Knappheit fossiler Energieträger) sowie politische Strategien (z.B. an Umweltaspekten ausgerichtete Verkehrssteuern, Nutzergebühren und Stadtplanung) begründen. Technologischer Wandel sorgt dafür, dass der verbleibende Verkehr nachhaltig wird. Wichtige Aspekte sind hier zum einen die weite Verbreitung effizienter An-triebstechnologien und Leichtbau und die damit einhergehende Einführung neuer Fahrzeugkonzepte sowohl im Personen- als auch im Güterverkehr. Zum anderen spielen die Optimierung und intelligente Gestaltung multimodaler Mobilitätskonzepte durch Informations- und Kommunikationstechnologien eine wichtige Rolle. Im Personenverkehr ermöglichen diese Technologien beispiels-weise einen Zugang zum jeweils optimalen Verkehrsmittel mit einheitlicher ii VIVER - Vision für nachhaltigen Verkehr in Deutschland Echtzeit-Buchungs- und Abrechnungsschnittstelle, im Güterverkehr ermögli-chen sie die effiziente Kombination verschiedener Transportmittel sowie einen deutlich optimierten Auslastungsgrad und besseres Routenmanagement. Auch die Kombination von Personen- und Gütertransport in einem Fahrzeug kann zukünftig an Bedeutung gewinnen. Die beschriebene Vision stellt das Ergebnis einer Entwicklung hin zu einem nachhaltigen Verkehrssystem anschaulich dar und kann die Kommunikation nachhaltiger Entwicklungsziele an relevante gesellschaftliche Zielgruppen un-terstützen und Anziehungskraft ausüben, statt Angst vor Veränderungen zu wecken.
urn:nbn:de:0011-n-1622844
Keywords: 330; Sustainability; mobility; transport; vision; Germany; 2030; 2050